Profesionalisme Guru Matematika MTs Muhammadiyah 22 Padangsidimpuan - Rangkuti, Ahmad Nizar; Jusrina, Jusrina (Universitas Islam Negeri Imam Bonjol Padang, 2017)
The purpose of this research to know the professionalism mathematics’ teacher in MTs Muhammadiyah 22 Padangsidimpuan. To collecting the data done by field research and the technique of the collecting the data, the researcher used Observation, Interview and Study Documentation. To analyze the data done by Qualitative Research. To valid the data used Triangulation. So, based on the result of this research, it could be concluded that the professionalisms mathematics’ teacher in MTs Muhammadiyah 22 Padangsidimpuan have going on based on role happened. It could be seen by the Commitment of Mathematics’ teacher were to increase the quality of education, responsibility of doing assignment, desire, and enthusiasm to increase the professionalism done by long live study and the soul of Mathematics.Keywords: Profesionalism, mathematics teacher.